(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Since the disintegration of the Soviet Union in 1989 allconditions and principles of doing business in the area has changed. The shiftfrom a planned economy to a market economy is connected with rapid and basicchanges in the political, social, economic and technological conditions in allthe Eastern European countries.